HISTORICAL ASPECT OF THE MENTAL PROBLEM STUDENT DEVELOPMENT - I.V. Lovyanova (Academy of Cognitive and Natural Sciences, 2022)
Approaches are analysed in article to decision of the problem of the mental development of the pupils in different history epoches, as well as their influence upon development and introduction modern technology education, oriented on personality of the pupil.